"Addiction Pharmacy" and the Professionalization Process: Technology-Enhanced Assessment of Reflective Practice and Teamwork - Cicely Roche (MDPI AG, 2014)
Professionalization of pharmacy students requires that they both recognize the dynamic social contract between the public and the profession and demonstrate themselves competent in professional attributes. This pilot aims to demonstrate and assess the attributes of reflective practice and teamwork in a manner that also demonstrates student recognition of the profession's responsibilities towards addiction to medicines. The assessment of a series of 8 weekly workshops on addiction pharmacy was adapted to include an online reflection, or journal entry, after each workshop. Groups of up to five students also collaboratively prepared a letter, in the format of an online wiki or editable website, to a choice of the Minister for Health, a national newspaper or a popular television chat-show. Groups aimed to influence decision-makers in a manner supportive of society's management of drug addiction. Online activity, grading and results of a student survey indicate that this novel assessment strategy provides a means by which aspects of the professionalization of pharmacy students might be effectively demonstrated and assessed. The article shares the assessment design, indicates how it may facilitate the demonstration and assessment of professional attributes, highlights the link with elements of the professionalization process and concludes that further investigations are merited.